Localised fault location on a distribution network – case studies and experience. Issue 15 (25th September 2018) - Courtney, David; Littler, Tim; Livie, Jim; Lennon, Ken
Abstract : A reduction in time required to locate and restore faults on a utility's distribution network reduces customer minutes lost. Detection of repeating transient (self‐clearing) faults allows early repair and avoids full faults which reduces the number of customer interruptions. Both these reductions bring improved customer service and direct cost savings from lower regulator penalties. Traditional approaches to fault location involve fault impedance determination from high‐volume waveform files dispatched across a communications channel to a central location for processing and analysis. This study describes an existing distributed scheme, where data processing is undertaken locally within substation‐based recording instruments thus reducing data volume transmission. Processed events/faults and impedance data are emailed to a central server for entry into the graphical information system, which returns potential fault locations yielding timely repair and restoration of circuits. This study presents a series of fault location case studies based on field experience from the Scottish Power Energy Networks distribution network.